Effects of dietary alpha-ketoglutarate: l-carnitine ratio on growth performance, nutrient metabolism and health status of oreochromis niloticus - Uzma Soharwardi (KUFOS, 2019)
Growing evidences reveal that some amino acids or their derivatives play important roles in the modulation of fish somatic growth, nutrient retention efficiency and antioxidant defense. In this context, 60 days feeding trial was carried out to evaluate the effects of dietary Alpha-ketoglutarate: L-carnitine ratio on growth performance, feed utilization, blood biochemical parameters, digestive enzymes, antioxidant status and nutrient metabolism enzymes of Oreochromis niloticus. The experimental design was completely randomized with six treatments including control each having three replicates. A total number of 360 healthy Oreochromis niloticus fry with an average individual weight of (1.39±0.01) were stocked in 18 plastic tanks (18 fishes in each tank) of 100 L capacity. Total six iso-nitrogenous (30% CP) iso-caloric (6% CL) feeds were prepared with Alpha-ketoglutarate : L-carnitine supplementation in the ratio of 0.9 : 0.1, 0.7 : 0.3, 0.5 : 0.5, 0.3 : 0.7, 0.1 : 0.9 respectively. Feed was provided ad libitum three times at 8:00 am, 12:30 pm and 4:30 pm daily. The results showed that supplemental dietary Alpha-ketoglutarate: L-catrnitine in the ratio of 0.1 : 0.9 and 0.3 : 0.7 significantly (P<0.05) affect the growth performance and nutrient utilization of Oreochromis niloticus fry. Group fed dietary Alpha-ketoglutarate: L- catrnitine in the ratio of 0.1 : 0.9 showed increased protein content and decreased lipid content (P<0.05). Serum triglyceride and cholesterol levels were significantly lower in group fed with 0.1 : 0.9 and 0.3 : 0.7 Alpha-ketoglutarate : L-catrnitine supplementation respectively. Also, Alpha-ketoglutarate: L-catrnitine supplementation in the ratio of 0.1 : 0.9 and 0.3 : 0.7 respectively elevated antioxidant enzyme activity (superoxide dismutase, SOD; glutathione S transferase, GST), protein ( glutamate dehydrogenase, alpha-ketoglutarate dehydrogenase) and lipid (malate dehydrogenase, carnitine acetyltransferase) metabolism enzymes. The digestive enzymes like protease and amylase also showed significant difference among the treatments. From the present study, it was concluded that the dietary Alpha-ketoglutarate: L-carnitine supplementation in the ratio of 0.1 : 0.9 and 0.3 : 0.7 resulted in enhanced growth performance, feed utilization, liver antioxidant status, digestive enzyme and nutrient metabolism activity of Oreochromis niloticus.